2020
DOI: 10.1038/s41556-020-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

A perinuclear microtubule-organizing centre controls nuclear positioning and basement membrane secretion

Abstract: Non-centrosomal microtubule-organizing centres (ncMTOCs) have a variety of roles presumed to serve the diverse functions of the range of cell types in which they are found. ncMTOCs are diverse in their composition, subcellular localization, and function. Here we report a perinuclear MTOC in Drosophila fat body cells that is anchored by Msp300/Nesprin at the cytoplasmic surface of the nucleus. Msp300 recruits the MT minus-end protein Patronin/CAMSAP, which functions redundantly with Ninei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 67 publications
3
80
0
Order By: Relevance
“…In contrast to the non-centrosomal ɣ-TuRC localization defects we observed in WDR-62 gut (-) or VAB-10B gut(-) embryos, we found that apical PTRN-1 signal was drastically decreased upon depletion of either VAB-10B or WDR-62 ( Figure 5D). This result is consistent with several reports of spectraplakins targeting Patronin/CAMSAP to ncMTOCs in various cell types (Ning et al, 2016;Nashchekin et al, 2016;Zheng et al, 2020) and is the first report of a role for WDR62 family proteins in PTRN-1 localization.…”
Section: Vab-10b and Wdr-62 Recruit Microtubule Minus End Proteins Tosupporting
confidence: 93%
“…In contrast to the non-centrosomal ɣ-TuRC localization defects we observed in WDR-62 gut (-) or VAB-10B gut(-) embryos, we found that apical PTRN-1 signal was drastically decreased upon depletion of either VAB-10B or WDR-62 ( Figure 5D). This result is consistent with several reports of spectraplakins targeting Patronin/CAMSAP to ncMTOCs in various cell types (Ning et al, 2016;Nashchekin et al, 2016;Zheng et al, 2020) and is the first report of a role for WDR62 family proteins in PTRN-1 localization.…”
Section: Vab-10b and Wdr-62 Recruit Microtubule Minus End Proteins Tosupporting
confidence: 93%
“…Overexpression of the SR1 domain of AKAP6, but not the SR1-3 domain, disrupted MTOC activity at the nuclear envelope of cardiomyocytes in a similar way as depletion of AKAP6 ( Figure 4—figure supplement 1A ). In accordance with the disruption of MTOC activity, AKAP6 depletion resulted in the release of γ-tubulin from the nuclear envelope ( Figure 4E ), the primary microtubule nucleator in centrosomes ( Akhmanova and Steinmetz, 2019 ), and ninein ( Figure 4F ), a microtubule-binding protein with anchoring function ( Mogensen et al, 2000 ) implicated in ncMTOC formation ( Goldspink et al, 2017 ; Ohama and Hayashi, 2009 ; Zheng et al, 2020 ). Notably, ninein remained associated with AKAP9-positive patches ( Figure 4F ), which retain microtubule nucleating activity ( Figure 4—figure supplement 1B ).…”
Section: Resultsmentioning
confidence: 52%
“…In Drosophila muscle and fat cells exhibit a perinuclear MTOC. Although both cell types are distinct in their molecular architecture and the mechanisms by which microtubule assembly is regulated, both require the nesprin-shot complex ( Wang et al, 2015 ; Zheng et al, 2020 ). Interestingly, AKAP6 has no homologue in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila tracheal cells, the microtubule-severing enzyme Spastin promotes the localization of microtubules and γTuRCs to the apical membrane, where the membrane protein Piopio facilitates their attachment [8]. Other subcellular structures that can become the main MTOC include mitochondria (spermatids in Drosophila [161]) and the nuclear envelope (Drosophila fat body cells [162] as well as striated muscle cells in Drosophila and mammals, see Section 4).…”
Section: Non-centrosomal Mtocsmentioning
confidence: 99%
“…While the ability of AKAP9 to recruit γTuRCs has been well described at the Golgi (see Section 3.3), it remains unclear why other γTuRC-interacting proteins do not contribute notably to microtubule nucleation at the nuclear envelope. Interestingly, a recent study in Drosophila showed that at the perinuclear ncMTOC of fat body cells, microtubule nucleation depends on the CAMSAP orthologue Patronin and the microtubule polymerase Msps (XMAP215 family member) but not on γ-tubulin [162]. Future studies should aim to dissect the contributions of γTuRCs and other microtubule polymerizing (e.g., XMAP215) or stabilizing (e.g., CAMSAPs, TPX2) factors to microtubule nucleation at the nuclear envelope of striated muscle cells.…”
Section: Anchoring Of Centrosomal Proteins and Control Of Microtubulementioning
confidence: 99%